MEMBACA: SEBAGAI MEDITASI PIKIRAN DAN BAHASA - Chaer, Hasanuddin; Sirulhaq, Ahmad; Rasyad, Abdul (Pusat Pengembangan Bahasa IAIN Tulungagung, 2019)
The concept of metacognitive learning with a spiritual approach is to focus on the role of mind and language and how to apply it in reading to improve emotional of intelligence in understanding the universal meaning of the text. This essay uses the approach Centered Attention of Meditation (FA). That is to focus the mind on objects, images, or words in sentences that are understood to add insight to the context of what the author explained, to connect the reader to understand the mind and language. This essay is here to open the freezing of the universal meaning of the text from what covers the mind and the meaning of language with the reading formula (B+B), namely “Stop and Think”. Human language is a linguistic structure that must be understood through understanding of meditation.